Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages therefore, must have the last word, but not the only word, so long as they remain in charge. Workers' Control must, then, to a degree be indirect and incomplete. They must, for instance, be heavily represented, if not in a majority, on the Regional Boards which under Common Ownership will be responsible, among other things, for the appointment and dismissal of managers. But just as in the factory the worker, although fully entitled to be consulted on production matters, cannot be in full control, so the National Boards, although containing heavy representation from the industrial side — workers plus management — must not be able to over-ride the decisions of the National Economic Council which Parliament must set up to plan our economic life as a whole. The ultimate residence of Workers' Control must be in Parliament itself. However, while management must be protected from undue interference in the performance of its difficult duties, it is equally certain that under Socialism the worker is entitled to freedom from arbitrary dismissal. It must be a rule that under no circumstances shall a dismissal by an immediate superior be carried out without reference to "higher authority," while dismissal for disciplinary reasons must be sanctioned by the workers themselves. Clearly, if the Socialist State is to avoid the extremes of Syndicalism and Bureaucracy in industrial life, a compromise between "pure" democracy and managerial autocracy must be found. The proportions of each in the final blend is the important point. Examples of Industrial Democracy It is most urgent that all Socialists should realise that the need for the active participation of workers in the control of their own employments, in the interests of efficiency, is now recognised by all genuinely progressive managements, so much so that half-hearted, apologetic advocacy by Socialists will leave them in the rear-guard of progressive thought in this vital sphere. The Soviet State has long proclaimed that much of its success in the work of reconstruction has been due to economic democracy. Stakhanovism apart, it is known that Gosplan makes much use of the detailed experience of the "man-on-the-job" in the formulation of the Five-Year Plans. But those Socialists who distrust Soviet examples will probably listen more readily to a voice from America — that of David Lilienthal, describing the methods of the Tennessee Valley Authority: "The spiritual yields of democratic methods, a renewed sense that the individual counts, would be justification enough. " The people must be in on the job.... Efficiency,... 20 15X/2/98/21